The horse boy : a father's quest to heal his son - Isaacson, Rupert (New York : Little, Brown and Co., 2009)
When his son Rowan was diagnosed with autism, Rupert Isaacson was devastated, afraid he might never be able to communicate with his child. But when Isaacson, a lifelong horseman, rode their neighbor's horse with Rowan, Rowan improved immeasurably. He was struck with a idea: why not take Rowan to Mongolia, the one place in the world where horses and shamanic healing intersected?
Keywords: Isaacson, Rowan; Isaacson, Rupert; Autistic children -- United States -- Biography; Parents of autistic children -- United States -- Biography; Autism in children -- Treatment -- Case studies; Horses -- Therapeutic use -- Case studies; Human-animal relationships -- Case studies; Autistic children -- Family relationships -- Case studies; Fathers and sons -- Case studies; Austin (Tex.) -- Biography